ANALYSIS OF TEACHERS 'PROFILE OF SCHOOL X: TRAINING AS AN INSTRUMENT OF FORMATIVE EVALUATION (Fiep Bulletin - online, 2019)
The approval of the Law on Guidelines and Bases of Brazilian Education (Law No. 9394/96) was a major advance forthe role of the school in the Brazilian social context, its main characteristic being that it is a law in the service of the student.Therefore, this article aims to analyze the profile of teachers and specific objectives to verify and intervene in the practices andconceptions in the evaluation process in search of awareness of each teacher about the role that the evaluation occupies in thisschool setting. To improve the performance of the learner it is necessary to break with the role of classification and selection thatthe evaluation fulfilled in the 60s and 70s and to act in the promotion of formative evaluation, an instrument of inclusion andmonitoring of the level of learning. Therefore, in proving that in the Political Project Pedagogical (PPP) of the State School "DoLajão" there was no clear insertion of the process of formative evaluation was carried out the research focused on the educatorsof this school. The methodology used in the present study was action research, with the application of questionnaires andinterviews. We present the results of the research that verified with these educator's information about the evaluation processused, allowing the actions carried out with the objective of knowing, discussing and implementing the formative evaluationprocess. The final analysis of the results of the research is done indicating the objectives achieved and suggestions for theevaluation to be really an instrument for the evaluation of these students.